Increasing of post-freezing quality of Spermatogonial Stem Cells after pretreatment by vitamin E - Aliakbari, Fereshte; Heidari, Mohammadhossein; Hossini, Mohammad Ali; Hosseini, Jalil (Archives of Men's Health, 2019)
Introduction: Mouse spermatogonial stem cells (SSCs) can be cryopreserved for long periods while preserving their spermatogenic ability. Although cryopreservation has been found to increase reactive oxygen species (ROS) formation that damages cellular structures. In the present study, we added vitamin E to the basic freezing medium in order to evaluate its effect on the efficiency of spermatogonial stem cells. Methods: SSCs isolated from testes of 6 days old male mice by enzymatic digestion. Vitamin E 100, 200, 400 µg/mL was added to the basic freezing medium. The cell viability was evaluated by MTT assay. After thawing, SSCs were cultured for 1 month and the expression pattern of specific genes of SSCs measured by real-time PCR technique. Results: The survival rate of the freeze cells in the presence of vitamin E was significantly higher than the control group (p<0.05). The number of colonies and their diameter measured after one month were significantly higher in the vitamin E groups than in the control group (p≤0.05). Conclusion: Adding vitamin E to the basic freezing medium thus can be helpful in increasing the quality and viability of SSCs after cryopreservation.